2013
DOI: 10.1016/j.ijfatigue.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of residual stress relaxation and its effect on fatigue strength of AISI 316L stainless steel ground surfaces: Experimental and numerical approaches

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This paper is aimed at evaluating the residual stress relaxation and its effect on the fatigue strength of AISI 316L steel ground surfaces in comparison to electro-polished surfaces. An experimental evaluation was performed using 3-point and 4-point bending fatigue tests at R r = 0.1 on two sets of notched specimens finished by electro-polishing and grinding. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 27 publications
(44 reference statements)
4
44
0
Order By: Relevance
“…Moreover, the majority of fatigue predictive methods take into account the initial measured residual stress values and neglect their evolution under cyclic loading. This assumption is controversial by published data related to stabilized residual stress profiles showing relaxation and redistribution phenomena [2, 8,12,13]. Moreover, it has been reported that the most fraction of residual stress relaxation is monotonic, since it occurs at first cycles.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the majority of fatigue predictive methods take into account the initial measured residual stress values and neglect their evolution under cyclic loading. This assumption is controversial by published data related to stabilized residual stress profiles showing relaxation and redistribution phenomena [2, 8,12,13]. Moreover, it has been reported that the most fraction of residual stress relaxation is monotonic, since it occurs at first cycles.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that the machining surface integrity influences strongly the fatigue lifetime of materials, since fatigue micro-cracks initiate always at the surface [12][13][14][15][16][17]. For this reason, several studies have been dedicated to the effects of milling on fatigue behaviour of many materials, particularly aluminium and titanium alloys, and superalloys widely used to manufacture structural parts for aviation and aerospace industries [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is necessary to ovoid tensile residual stresses occurring during the machining process. However, when the cyclic loading produces plastic deformation, the effect of residual stress will be reduced or disappeared [15,27]. In view of the high-speed milling process of Ti-10V-2Fe-3Al, Yao et al [28] found that the fatigue life of the workpiece is more sensitive to residual stress than to surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Residual stress is one of the most important factors in assessing the surface integrity of a ground component [18,19] because improper distributions of residual stresses will remarkably influence the service life and reliability of the component [20][21][22]. For this reason, characterization and prediction of grinding-induced residual stresses have been vital to the advanced design and fatigue failure analysis of components for aerospace, aviation, and automotive applications [23].…”
Section: Introductionmentioning
confidence: 99%